Osthole prevents tamoxifen-induced liver injury in mice - Zhou, Wen-bo (Acta Pharmacol Sin, 2018)
Tamoxifen (TMX) is an antiestrogen drug that is used in the treatment and prevention of all stages of estrogen-dependent breast cancer. Adverse effects of TMX include hepatotoxicity. In this study, we investigated the therapeutic effects of osthole, isolated from medicinal plants especially Fructus Cnidii, on TMX-induced acute liver injury in mice. Mice were injected with osthole (100 mg/kg, ip) or vehicle, followed by TMX (90 mg/kg, ip) 24 h later. We showed that a single injection of TMX-induced liver injury and oxidative stress. Pretreatment with osthole attenuated TMX-induced liver injury evidenced by dose-dependent reduction of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities. Pretreatment with osthole also blunted TMX-induced oxidative stress, evidenced by significant increase of reduced glutathione (GSH) as well as reduction of malondialdehyde (MDA) and hydrogen peroxide (H(2)O(2)). Consistently, osthole significantly enhanced the expressions of antioxidant genes (GPX1, SOD2, GCL-c, and G6pdh), but suppressed those of pro-oxidant genes (NOX2 and ACOX). Furthermore, osthole inhibited the production of inflammatory cytokines, reduced the metabolic activation of TMX, and promoted its clearance. We further revealed that osthole elevated hepatic cAMP and cGMP levels, but inhibition of PKA or PKG failed to abolish the hepatoprotective effect of osthole. Meanwhile, prominent phosphorylation of p38 was observed in liver in response to TMX, which was significantly inhibited by osthole. Pretreatment with SB203580, a p38 inhibitor, significantly attenuated TMX-induced increase of ALT and AST activities, reduced oxidative stress, and reversed the alterations of gene expression caused by TMX. Moreover, pretreatment with L-buthionine sulfoximine (BSO), an inhibitor of GSH synthesis, partly reversed the effect of osthole on TMX-induced liver injury. Consistently, pretreatment with N-acetyl-L-cysteine (NAC) significantly attenuated TMX-induced increase in ALT and AST activities. Notably, both BSO and NAC had no detectable effect on the phosphorylation levels of p38. Collectively, our results suggest that osthole prevents TMX hepatotoxicity by suppressing p38 activation and subsequently reducing TMX-induced oxidative damage.